THE INFLUENCE OF UTILIZING CHATGPT AS A DIGITAL LEARNING MEDIA ON STUDENTS’ LEARNING MOTIVATION AND ACHIEVEMENT IN LEARNING ENGLISH - Sri Handayani; Anhar Nur Hidayah; Sumardiono (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study aims to examine the influence of ChatGPT as a digital learning media on students' learning motivation and achievement in English towards eleventh-grade students at MAN 1 Surakarta in the 2024/2025 academic year. The research employed a quantitative approach with a One-Group Pretest-Posttest design. The sample consists of 34 students selected through a random sampling technique. Data collection instruments include test and questionnaires to measure the impact of ChatGPT on students' motivation and achievement in English. Data analysis is conducted using a paired sample t-test with the assistance of the IBM SPSS Statistics 25 software. The findings reveal a statistically significant influence of ChatGPT on students’ learning motivation and achievement in English. Based on the paired sample t-test analysis, the t-count value for the questionnaire is 8.879, while for the test, it is 16.062. When compared to the t-table value at a degree of freedom (df) of 33 (n-1) with a 5% significance level (2.035), both t-count values exceed the t-table value (8.879 > 2.035 and 16.062 > 2.035). These results lead to the rejection of Ho and the acceptance of Ha, indicating that ChatGPT has a significant influence on students' motivation and academic achievement in English learning.